Transition metal-catalyzed alkene isomerization as an enabling technology in tandem, sequential and domino processes. (9th December 2020) - Fiorito, Daniele; Scaringi, Simone; Mazet, Clément
Abstract : One-pot reactions based on catalytic isomerization of alkenes not only offer the inherent advantages of atom-, step- and redox-economy but also enable the preparation of value-added products that would be difficult to access by conventional methods. Abstract : One-pot reactions elaborated around transition metal-catalyzed isomerization of alkenes not only offer the inherent advantages of atom-, step- and redox-economy but also enable the preparation of value-added products that would be difficult to access by conventional methods. In this Review, we cover seminal and recent examples of tandem, sequential and domino processes, which incorporate the most attractive features of olefin isomerization.